Intracallus cytotypic variation of regenerated Oryza sativa L. plants in the in vitro androgenesis - M. V. Ilyushko (Труды по прикладной ботанике, генетике и селекции, 2025)
Background. The in vitro androgenesis has proven to be a reliable method for obtaining doubled haploids for many plant species. In the breeding of Oryza sativa L., in vitro culture of anthers is used, which go through the stage of callus formation followed by regeneration. The ratios between cells of different types and green regenerated plantlets on the callus might not coincide, since not all genetic disorders that accumulate in the in vitro culture at the cellular level can go through the stage of morphogenesis and cannot always lead to regeneration. The objective of the study was to assess the frequency of intracallus cytotypic variability of regenerated O. sativa plants in the in vitro androgenesis.Materials and methods. We studied regenerated plantlets obtained on O. sativa calli through the in vitro androgenesis of thirty F1 and F2 hybrids. According to their morphological features, regenerated plants were divided into five cytotypic groups: haploids, doubled haploids, aneuploids, tetraploids, and plants that died in the early stages of growth and development.Results. The experiment employed 409 calli with multiple regenerations. Only haploid plants were formed on 79 calli, only doubled haploids on 60 calli, only aneuploids on three calli, only dead plantlets on one callus, and only tetraploids on two calli. It was established that 265 (64.8%) calli were polymorphic. The calli polycytotypicity with two types of regenerated plants, excluding the dead ones, was 138 pcs. (33.7%), with three types 62 pcs. (15.2%), and with four types 7 pcs. (1.7%). The differences between the calli of the F1 and F2 hybrids were highly significant in the haploids, doubled haploids, tetraploids, and dead regenerated plants (p < 0.0002). An increase in the number of regenerated plantlets per callus occurred due to the presence of haploid plants; the correlation coefficient was r = 0.81 (p < 0.05).Conclusion. The intracallus cytotypic variability of O. sativa in the in vitro androgenesis was 64.8%, which was comparable to the proportion of the calli with different cell ploidy.